2-local Lie *-automorphisms on factors. Issue 11 (2nd November 2018) - Liu, Lei
Abstract: Let be a factor which is not of type . We prove that every surjective 2-local Lie *-automorphism of can be written in the form, where is an *-automorphism or the negative of an anti-*-automorphism, and h is a *-linear functional vanishing on all finite sums of commutators.